Improving Indonesian Language Learning Results Through The Demonstration Method On The Materials to Find Vocabulary Related to Unhealthy Environment Class II SDN 01 Pasir - Mitsni Soifah (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This study entitled "Improving Indonesian Language Learning Outcomes through demonstration methods of vocabulary materials related to the unsanitary environment of Class II SDN 01 Pasir". The purpose of this research is to improve student learning outcomes in Indonesian lessons. The research conducted was classroom action research (PTK). The stages are planning, implementing, observing, and reflecting. As for the indicator of increasing the ability of class II SDN 01 Pasir students, it was shown the acquisition of scores in the pre-cycle with a percentage of 21.05% that had been completed. Then there was an improvement in learning cycle 1, it was shown that there was an increase with the percentage of 52.63% that had been completed, so the researcher carried out the second cycle by obtaining a significant increase with the percentage value of 97.3% that had been completed. The results show that the demonstration method can improve student learning outcomes, especially in class II Indonesian language lessons at SDN 01 Pasir.